ANALISIS SHARIA GOVERNANCE AND STRUKTUR MODAL TERHADAP TINGKAT KEPATUHAN SYARIAH BERDASARKAN STANDAR AAOIFI - Tazkiya, Hasina; Muhammad, Rifqi (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study aims to analyze the influence competency of SSB, SSB size, board of directors meetings, board tenure, audit committee, firm size, and leverage on the level of disclosure of sharia compliance based on AAOIFI standards in Indonesia and Malaysia for the period 2011-2020 using DPS disclosure based on AAOIFI Governance Standard No. 1 and 5. The population of this study were Sharia commercial banks in Indonesia and Malaysia using purposive sampling method. Data analysis was performed by panel data regression. The results showed that the variable competence of DPS, the number of DPS, and the board of Directors meeting a positive effect on sharia compliance. While the variable tenure of the board of Directors, audit Committee, firm size, and leverage does not affect sharia compliance